PENGENALAN MEREK PEMASARAN PADA USAHA KRIPIK PISANG IBU ARI (Studi kasus di Jln. Puyang Sakti Kota Manna ) - Ameilia, Deva; Afriani, Sulisti; yanti, Rina Trisna; nasution, Suswati (Jurnal Dehasen Mengabdi, 2023)
Brand recognition marketing is promoting a brand's product or service in a way that elevates the brand as a whole. This involves creating and maintaining brand-consumer relationships and marketing brand attributes traits that people develop when they describe a particular brand. In this guide, Brand or brands are able to create interactive communication with consumers. The stronger a brand, the stronger the interaction with consumers. In order to introduce a brand or brands to the public, including brands, especially the local Ibu Ari banana chip business, by way of popularizing the brand, one of which is a marketing communication strategy, which is a marketing activity that seeks to disseminate information, persuade, increase the target market so that the product is accepted.The implementation of marketing brand recognition is carried out in several steps, such as creating a brand identity for Ibu Ari's banana chip business and using social media. The brand identity was created to introduce the Ibu Ari banana chip brand more clearly and up to date in the market, while the use of social media was made so that consumers could easily recognize and remember the Ibu Ari brand and give a positive image to the brand.From the results of the evaluation, the community service program entitled "Marketing Brand Recognition in Ibu Ari's Banana Chips Business" succeeded in having a positive impact on the continuity of the business. Debfab thus implementing effective marketing brand recognition can be a solution for businesses in facing increasingly competitive competition.